Scaling readiness: Science and practice of an approach to enhance impact of research for development - Sartas, Murat; Schut, Marc; Proietti, Claudio; Thiele, Graham; Leeuwis, Cees (Elsevier, 2020)
Scaling of innovations is a key requirement for addressing societal challenges in sectors such as health, agriculture, and the environment. Research for development (R4D) programs, projects and other interventions struggle to make particular innovations go to scale. Current conceptualizations of scaling are often too simplistic; more systemic and multidimensional perspectives, frameworks and measures are needed. There is a gap between new complexity-aware theories and perspectives on innovation, and tools and approaches that can improve strategic and operational decision-making in R4D interventions that aim to scale innovations. This paper aims to bridge that gap by developing the key concepts and measures of Scaling Readiness. Scaling Readiness is an approach that encourages critical reflection on how ready innovations are for scaling and what appropriate actions could accelerate or enhance scaling. Scaling Readiness provides action-oriented support for (1) characterizing the innovation and innovation system; (2) diagnosing the current readiness and use of innovations as a proxy for their readiness to scale; (3) developing strategy to overcome bottlenecks for scaling; (4) facilitating and negotiating multi-stakeholder innovation and scaling processes; and (5) navigating and monitoring the implementation process to allow for adaptive management. Scaling Readiness has the potential to support evidence-based scaling strategy design, implementation and monitoring, and – if applied across multiple interventions – can be used to manage a portfolio of innovation and scaling investments.